ASUHAN KEBIDANAN KOMPREHENSIF PADA NY. H DI PUSKESMAS 9 NOPEMBER BANJARMASIN TIMUR - Aprilita Jalastri; Nur Cahyani Ari Lestari (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2022)
According to Indonesian Demographic and Health Survey 2017, Maternal Mortality Rate related to pregnancy, childbirth and postpartum period is 265/100,000 live births, while infant mortality rate is 27/1,000 live births. Puskesmas November9, 2020, target was 428 pregnant women, 65.4% pure K1 achievement, 61% KF, 71.4% KF, 80.92% KN, 62 referred risks or complications, risk detection obtained by health workers as many as 18 people, risk detection obtained from the community as many as 95 people and the number of active family planning participants as many as 2781 people. In reducing MMR and IMR, as well as preventing complications in pregnancy and childbirth, early detection of high risk is very necessary with t support of quality services and other events such as counseling, classes for pregnant women and comprehensive care. Objective: To carry out comprehensive midwifery care for Mrs. H from pregnancy to family planning. Research method used case study by understanding condition of client and problems faced by Mrs. H 31 years G3P2A0 UK 34 weeks, conducted in October 2020-January 2021, data collection is observation, interviews, measurements and documentation using case study instruments in the form of SOAP. Based on the assessment during pregnancy, Mrs. H is normal and has no complaints. Evaluation of client in good and normal condition. Smooth delivery. Baby was born normal, during visit no problems were found. Uterine involution is normal and there are no complaints. KB care for Mrs. H plans to take lactation pills. Care provided is in accordance with standard of care